A world key to Cryptothecia and Myriostigma (Arthoniaceae), with new species and new records from the Andaman and Nicobar Islands, India - Ram, T. A. M. Jagadeesh; Sinha, G. P. (Phytotaxa, 2016)
A world key to the genera Cryptothecia and Myriostigma is presented. Four species of Cryptothecia: C. albomaculans, C. elata, C. elongata and C. superphyllinica, and a Myriostigma: M. nicobaricum are described as new to science from the Andaman and Nicobar Islands, India. Cryptothecia albomaculans has a heteromerous thallus, whitish ascigerous areas not elevated above the thallus, ellipsoid, 9–11 × 3–5 septate ascospores of 47–57 × 24–30 µm and produces 2’-O-methylperlatolic acid. Cryptothecia elata has a homoiomerous thallus with distinctly raised ascomata, ascospores of (72–)84–122 × (25–)36–62(–72) µm and contains 2’-O-methylmicrophyllinic acid. Cryptothecia elongata has a heteromerous thallus, raised, irregular, 1–4 mm wide ascigerous areas covered by a photobiont layer, narrowly ellipsoid-oblong, 16–24 × 2–6 septate ascospores of 90–114 × 21–30 µm, and produces gyrophoric and lecanoric acids. Cryptothecia superphyllinica has a homoiomerous thallus, whitish, raised, rounded to linear ascigerous areas 0.5–1.5 mm in diam., broadly ovoid to ellipsoid, 9–15 × 3–6 septate ascospores of (45–)58–76(–80) × (22–)24–33(–38) µm and 2’-O-methylsuperphyllinic acid. Myriostigma nicobaricum has a homoiomerous thallus, whitish, raised, rounded, ascigerous areas 0.3–0.8 mm in diam.,  broadly ellipsoid to ovoid, 8–11 × 2–4 septate, 34–48 × 16–22 µm ascospores and confluentic acid. Cryptothecia aleurodes, C. eungellae and C. striata are new additions to the lichen biota of India. Ascospores of Cryptothecia eungellae are described for the first time and illustrated.